Developing the "Control Identity" Typology to Create More Effective Testicular Health Promotional Messaging. Issue 3 (May 2018) - Rovito, Michael J.; Gordon, Thomas F.; Bass, Sarah B.; DuCette, Joseph; Tierney, Ashley M.; Coles, Nicholas
Testicular self-examination (TSE) promotional interventions historically operate without a theoretical framework, which negatively influences their effectiveness. As TSE is critical to the early detection of testicular cancer, this behavior is an essential component to improving overall male well-being. To address this need, the Control Identity personality typology was developed to assist in creating more effective TSE promotional interventions. Four outcome control dispositions were defined a priori based on the dimensions of illusions of control and locus of control. An original 41-item survey, the Control Identity Assessment Scale, was used to assess perceived vulnerability, value of health promotion, and health outcome control among a convenience sample of 300 university males aged 18 to 35 years via a cross-sectional research design. Factor and cluster analyses were employed to extract salient factors in the data and to identify subgroups within the sample. A consistent five-factor structure matrix (~70% explained variance) served as the foundation from which a k-means cluster analysis was employed to classify four types of individuals. Significant differences were detected between clusters on primary variables, including behavioral intentions to conduct TSE. The Control Identity typology aims to provide the needed mechanism for health practitioners to create more effective preventive health messaging to promote TSE. Future implications on employing this typology to segment audiences in order to increase overall effectiveness are offered. Application of this typology could ultimately lead to increasing TSE knowledge retention, behavioral intentions, actual performance, and adherence.